ASPEK GIZI DAN MAKNA SIMBOLIS TABU MAKANAN IBU HAMIL DI INDONESIA - Bibi Ahmad Chahyanto; Arnati Wulansari (JURNAL EKOLOGI KESEHATAN, 2018)
ABSTRACT The period of pregnancy is an important period early in the human life cycle, so the nutritional status and health must be optimized. The problem that many occur in pregnant women is the restriction of the type and amount of food consumed. One of them is due to food taboos. The purpose of this study was to describe the type of food taboos, symbolic meaning of food taboos on pregnant women in Indonesia, and its nutritional aspects. This study was a literature review, by collecting articles through the database online. Number of articles or libraries that have been collected to be reviewed were 38 reading materials, consist of 19 scientific articles, 10 research result in the form of thesis / dissertation, and 9 research result book with ethnographic approach. The results showed that the most abundant food taboos by pregnant women is the group of animal food dishes that are useful for fetal growth and development, such as squid and catfish. It is necessary to educate primarily on pregnant women to begin to avoid food taboos, and the importance of protein intake for fetal development early in human development cycle. Keywords: Nutrition, pregnant woman, symbolic meaning, food taboos ABSTRAK Periode kehamilan merupakan periode penting di awal siklus kehidupan manusia, sehingga status gizi dan kesehatannya harus dioptimalkan. Masalah yang banyak terjadi pada ibu hamil adalah pembatasan jenis dan jumlah makanan yang dikonsumsi. Salah satunya dikarenakan tabu makanan. Tujuan penelitian ini adalah mendeskripsikan jenis makanan yang ditabukan, makna simbolis tabu makanan bagi ibu hamil di Indonesia, dan aspek gizinya. Penelitian ini merupakan literature review, dengan mengumpulkan artikel melalui database secara online. Jumlah artikel atau pustaka yang berhasil dikumpulkan untuk ditelaah sebanyak 38 pustaka, terdiri dari 19 artikel ilmiah, 10 hasil penelitian berupa skripsi/tesis/disertasi dan 9 buku hasil penelitian dengan pendekatan etnografi. Hasil penelitian menunjukkan bahwa makanan yang paling banyak ditabukan oleh ibu hamil adalah kelompok makanan lauk hewani yang berguna bagi pertumbuhan dan perkembangan janin, seperti cumi-cumi serta ikan lele. Perlu adanya edukasi terutama terhadap ibu hamil untuk mulai menghindari tabu makanan dan pentingnya asupan protein untuk perkembangan janin di awal siklus perkembangan manusia. Kata kunci: Gizi, ibu hamil, makna simbolis, tabu makanan